GALLSTONE DISEASE WITH UNCONJUGATED HYPERBILIRUBINEMIA: CLINICAL APPROACH TO GILBERT’S SYNDROME - Suneed Kumar; Sneha Jha; Anshuman Pandey; Shibumon M Madhavan; Dinesh Kumar; Smita Chauhan; Shakeel Masood (Journal of Surgical Sciences, 2019)
Gallstones are the commonest ailment affecting the hepato-biliary system. Associated jaundice is usually direct, commonly due to biliary obstructive lesions. Unconjugated hyperbilirubinemia with cholelithiasis is commonly seen with hemolytic disease. In the absence of hemolysis or systemic causes, congenital causes prevail, commonest of which is Gilbert’ Syndrome. This study aims to ascertain a clinical approach to the patient of gallstones with Gilbert’s syndrome. This is retrospective study of 58 patients with gallstone associated unconjugated hyperbilirubinemia, who underwent surgery over a two-year period. Patients underwent repeat blood investigations and ultrasound to confirm the diagnosis. Obstructive biliary pathology was ruled out by MRCP images; EUS added if indicated. The remaining patients underwent genetic test for Gilbert’s syndrome – namely UGT1A1 gene assessment by PCR. All patients underwent laparoscopic cholecystectomy as routine; with addition of intra-operative liver biopsy. Sixteen of the 58 patients were short-listed to be high risk factors for harboring Gilbert’s syndrome after ruling out other systemic causes. On gene study, 14 patients tested positive for UGT1A1 gene, hence Gilbert’s syndrome. The other two were kept on follow up for jaundice recurrence in future. The management algorithm is depicted as flowchart. Gilbert’s syndrome can be identified in select “high-risk” individuals presenting with gallstone disease. Genetic testing is gold standard, and helps in effective management and better patient counselling.